Cytotoxic T lymphocytes in regional lymph nodes in colon cancer - V. V. Kryukova; V. L. Tsepelev; P. P. Tereshkov (Acta Biomedica Scientifica)
Background. The study of the subpopulation composition of cytotoxic T lymphocytes and the expression of co-inhibitory proteins on their surface in regional lymph nodes is necessary for the development of new methods of targeted therapy for colorectal cancer (CRC). The aim. To assess the subpopulation composition of cytotoxic T lymphocytes and the expression of co-inhibitory molecules on their surface in regional lymph nodes in patients with colon cancer. Methods. The relative content of cytotoxic T lymphocytes in regional lymph nodes, the subpopulation composition of cytotoxic T lymphocytes, and the expression of immune checkpoints (CTLA-4, PD-1, TIM-3) by CD8-positive cells in 105 patients with stage III colorectal cancer were determined using flow cytometry. The control group consisted of 75 patients who underwent colon surgery for non-neoplastic diseases. Results. In patients with CRC, the number of naive CD8+ lymphocytes (CD3+CD8+CD45RA+CCR7+) in regional lymph nodes decreases by 1.6 times, the relative content of cytotoxic T lymphocytes of effector memory (CD3+CD8+CD45RA-ССR7-) increases by 2.6 times, and the relative content of CD8-positive cells expressing CD57 on their surface increases by 2.6 times. In patients with CRC, on the surface of CD3+CD8+ lymphocytes of regional lymph nodes, the expression of the co-inhibitory molecule CTLA-4 increases by 4.5 times, PD-1 by 2.2 times, and TIM-3 protein by 1.7 times. Conclusion. In patients with colorectal cancer, the subpopulation composition of cytotoxic T lymphocytes in regional lymph nodes changes, which is expressed in a decrease in the proportion of naive cells and an increase in the relative content of effector memory cells. In CRC, the expression of co-inhibitory molecules (CTLA-4, PD-1 and TIM-3) on cytotoxic T lymphocytes in regional lymph nodes increases.